2018
DOI: 10.3390/sports6030085
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Longitudinal Changes in Body Composition by Sport-Position in NCAA Division I Basketball Athletes

Abstract: The purpose of this study was to assess the body composition of male and female basketball athletes (n = 323) across season, year, and sport-position using air displacement plethysmography. An independent sample t-test assessed sport-position differences. An analysis of variance was used to assess within-subjects across season (pre-season, in-season, and off-season), and academic year (freshman, sophomore, and junior). For both men and women basketball (MBB, WBB) athletes, guards had the lowest body fat, fat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 34 publications
8
26
0
Order By: Relevance
“…Similarly, researchers have primarily used skinfold calipers [3,5,27,28], ADP [8,9], and hydrostatic weighing [3,26] to examine female basketball athletes' total body composition, while fewer researchers [22,24] have utilized DXA to examine these athletes' total and regional body composition. Studies using hydrostatic weighing reported female basketball athletes to have greater total-body fat-free mass compared to athletes of other sports [26] and to non-athletes [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, researchers have primarily used skinfold calipers [3,5,27,28], ADP [8,9], and hydrostatic weighing [3,26] to examine female basketball athletes' total body composition, while fewer researchers [22,24] have utilized DXA to examine these athletes' total and regional body composition. Studies using hydrostatic weighing reported female basketball athletes to have greater total-body fat-free mass compared to athletes of other sports [26] and to non-athletes [3].…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies examining male and female basketball athletes' total body composition have used skinfolds, bioelectrical impedance (BIA), air displacement plethysmography (ADP), or hydrostatic weighing [1][2][3][4][5][6][7][8][9]. Importantly, the two-component body composition methods used by these previous studies are less accurate (up to 5 % error) than dual X-ray absorptiometry (DXA) [10].…”
Section: Total and Regional Body Composition Of Ncaa Division I Collementioning
confidence: 99%
“…Body composition is one of many factors that influences athletes’ sports performance and overall health and is commonly assessed as part of an athlete’s standard of care while competing at the collegiate level [ 1 , 2 , 3 , 4 , 5 ]. Body composition is related to many different health outcomes, including altered bone remodeling and endocrine functioning at low levels of body fat, and increased risk of metabolic comorbidities, such as dyslipidemia and insulin resistance with excessive body fat [ 1 , 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body composition is one of many factors that influences athletes’ sports performance and overall health and is commonly assessed as part of an athlete’s standard of care while competing at the collegiate level [ 1 , 2 , 3 , 4 , 5 ]. Body composition is related to many different health outcomes, including altered bone remodeling and endocrine functioning at low levels of body fat, and increased risk of metabolic comorbidities, such as dyslipidemia and insulin resistance with excessive body fat [ 1 , 2 , 6 ]. Although these outcomes are important to consider with athletes, as they could affect overall health and athletic performance, body composition assessment in sports medicine is often focused on much smaller variations in body composition, which are thought to affect athletic performance and injury risk [ 1 , 2 , 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…An additional three studies in the Special Issue identified game-related statistics explaining game outcomes and regional differences in various elite competitions (Olympics [12], EuroBasket [13], and Continental Championships [14]). The remaining three studies described physical [15,16] and skill [17] attributes in various player samples. It should also be noted our Special Issue addresses an important issue of increasing research in female athletes, who have traditionally been under-represented in the literature compared to male basketball players, with seven of the eight original studies (88%) containing female basketball players.…”
mentioning
confidence: 99%